GENDERED HUMOR AND SARCASM IN US PRESIDENTIAL ELECTION CAMPAIGNS: A CASE STUDY OF FEMALE CANDIDATES - Azimova Marjona Salim qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract. This article examines the role of gendered humor and sarcasm in shaping the political narratives surrounding female candidates in U.S. presidential elections. It explores how female politicians navigate the complexities of humor to engage voters, critique opponents, and manage public perception, all while contending with societal expectations regarding femininity and authority.